Laboratory Diagnosis of Viral Diseases - FENNER, FRANK (Veterinary Virology, 1987)
Tests for the specific diagnosis of a viral infection in an animal are of two general types: (1) those that demonstrate the presence of the virus and (2) those that demonstrate the presence of specific viral antibody. The provision, by a single laboratory, of a comprehensive service for the diagnosis of viral infections of domestic animals is a formidable undertaking. There are about 200 individual viral species in some 20 different viral families that infect the eight major domestic animal species. If antigenic types within an individual viral species are considered and the number of animal species is broadened to include turkey, duck, and zoo and laboratory animals, then the number of individual viruses exceeds 1000. It is, therefore, not surprising that few single laboratories could have available the necessary specific reagents, skills, and experience for the diagnosis of such a large number of infections.